Ultrastructural, Sensory and Functional Anatomy of the Northern Elephant Seal (Mirounga angustirostris) Facial Vibrissae. (21st August 2017) - Smodlaka, H.; Galex, I.; Palmer, L.; Borovac, J. A.; Khamas, W. A.
Summary: Vibrissae (whiskers) play a key role in underwater orientation in foraging phocids through vibrotactile sensation processing. Our aim was to evaluate the structure of northern elephant seal (NES) vibrissae by means of light (LM) and transmission electron microscopy (TEM), in order to elucidate their function. Vibrissal follicles were processed using standardized laboratory methods and LM/TEM techniques. Individual follicular axonal numbers were counted and axonal diameter measured and averaged. NES have mystacial, rhinal, supraorbital and labial vibrissae. The vibrissal follicles are histologically subdivided into a ring, upper and lower cavernous sinuses (LCS). Each vibrissa is innervated by the deep vibrissal nerve. The average number of axons per large mystacial vibrissa is 1804 (±123), rhinal 985 (±241), supraorbital 1, 064 (±204) and 374 (±65) in labial vibrissa. The entire vibrissal system carries an estimated 148 573 axons, and mystacial vibrissae alone have 125 323 axons. Axonal conduction velocity for each vibrissal type is 55.26 m/s for labial, 56.58 m/s for rhinal and 35.88 m/s for mystacial vibrissae. TEM and LM revealed a plethora of mechanoreceptors within the vibrissal follicles: Merkel cell‐neurite complexes, lanceolate and pilo‐Ruffini end organs. A vast number of sensory axons projecting from the entire vibrissal system indicate that the vibrissal sensory area takes up a large proportion of phocids' somatosensory cortex. In conclusion, NES has highly sensitive and finely tuned vibrotactile vibrissal sense organs.